Pengaruh Temuan Audit, Opini Audit, dan Tindak Lanjut Hasil Audit Terhadap Tingkat Korupsi - Tania Angela; Marsellisa Nindito; Hera Khairunnisa (LPPM Universitas Negeri Jakarta, 2023)
This study aims to analyze the Effect of Audit Findings, Audit Opinions, and Follow-up Audit Results on the Level of Corruption. The dependent variable in this study is the Level of Corruption, and the independent variable in this study is Audit Findings, Audit Opinions, and Follow-up Audit Results. This study uses secondary data obtained from IHSP, TRLHP, and MA Report in 2019 - 2021. Samples were selected using the purposive sampling method with criteria that have been determined by researchers and obtained by a total of 195 districts or cities. The analysis method used is panel data regression analysis with the help of EViews program version 13. The results of this study show that audit findings have no effect on the level of corruption, audit opinions have a negative effect on the level of corruption, and follow-up audit results have a positive effect on the level of corruption.